The Effectiveness of Edmodo-Based Blended Learning in Improving Learning Outcomes in Islamic Religious Education among Indonesian High School Students - Efri Yunanda; Jasrial Jasrial (AL-ISHLAH: Jurnal Pendidikan, 2026)
The integration of digital technology into education has encouraged the adoption of blended learning to enhance student engagement and academic achievement. However, empirical evidence regarding the effectiveness of Edmodo-based blended learning in Islamic Religious Education and Character Education at the secondary school level remains limited.This study employed a quantitative approach using a quasi-experimental, non-equivalent control group pretest–posttest design. The participants consisted of 34 Grade XI students at SMAN 2 Hiliran Gumanti, Indonesia, selected through purposive sampling. Nineteen students in the experimental group received Edmodo-based blended learning, while 15 students in the control group received conventional instruction. Learning outcomes were measured using a 40-item multiple-choice achievement test. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and an independent-samples t-test.The experimental group achieved a higher mean posttest score (82.89) than the control group (66.00). The independent-samples t-test revealed a statistically significant difference between the two groups (p .05), indicating that the Edmodo-based blended learning model was more effective than conventional instruction in improving students’ learning outcomes.Edmodo-based blended learning provides a flexible and interactive learning environment that enhances students’ academic achievement in Islamic Religious Education and Character Education. Although the findings support the effectiveness of this instructional approach, the study was limited by its small sample size and single-school setting. Future research should involve larger and more diverse samples while examining additional educational outcomes, including learning motivation, self-regulated learning, and digital literacy.